Effects of short-term energy restriction on liver lipid content and inflammatory status in severely obese adults: results of a randomised controlled trial (RCT) using two dietary approaches - Baldry, Emma; Aithal, Guruprasad Padur; Kaye, Philip; Idris, Iskandar; Bennett, Andrew; Leeder, Paul C; MacDonald, Ian A. (Wiley, 2017)
Short-term very low energy diets (VLED) are used in clinical practice prior to bariatric surgery, however, regimens vary and outcomes for a short intervention are unclear. We examined the effect of two VLEDs; a food-based diet (FD) and meal replacement plan (MRP) (LighterLife) over two weeks in a randomised controlled trial (RCT). We collected clinical and anthropometric data, fasting blood samples, and dietary evaluation questionnaires. Surgeons took liver biopsies and made a visual assessment of the liver. We enrolled 60 participants and 54 completed (FD n=26, MRP n=28). Baseline demographic features, reported energy intake, dietary evaluation and liver histology were comparable between groups. Both diets induced significant weight loss. Perceived difficulty of surgery correlated significantly with the degree of steatosis on histology. Circulating inflammatory mediators: CRP, Fetuin-A and IL6 reduced pre to post diet. Diets achieved comparable weight loss and reduction in inflammatory biomarkers, perceived operative difficulty, and patient evaluation. NAFLD histology assessments post-diet were also not significantly different between diets. Results indicate effectiveness of short term very low energy diets and energy restriction irrespective of macronutrient composition although small sample size precluded detection of subtle differences between interventions.